Judicial Rechtsvinding in the Absence of Legal Norms: A Case Study on the Revocation of Child Adoption in Indonesia - Abd. Rahmad; Joni Zulhendra (Institut Agama Islam Negeri Curup, 2025)
In Indonesia, the legal framework provides a regulatory basis for the adoption of children, but remains silent on the possibility and procedure for revoking such adoption. This article examines the role of judicial rechtsvinding (legal discovery) in resolving legal disputes in the absence of explicit statutory norms, with a focus on the revocation of child adoption in Indonesia. Drawing on a case study of Decision No. 410/Pdt.G/2020/PN.Bdg issued by the Bandung District Court, the study analyzes how the judge employed the method of argumentum a contrario to construct legal reasoning that justified the cancellation of a legally recognized adoption. The analysis reveals that the court integrated both juridical and sociological considerations, placing the child’s best interests at the center of its decision. This case illustrates how judicial discretion can function as a form of normative governance, especially in areas of law where legislative silence prevails. It also underscores the evolving role of the judiciary in shaping family law jurisprudence and filling legal gaps with ethically grounded reasoning. The findings contribute to the discourse on judicial activism, progressive legal interpretation, and child protection in civil law systems.